Peluang dan Tantangan Implementasi Kebijakan Desentralisasi Pendidikan - Tengku Darmansah; Irma Tussa’diyah Hasibuan; Khansa Arista Widya Maulida; Zuchairunnisa Zuchairunnisa (BADAN PENERBIT STIEPARI PRESS, 2025)
The education decentralization policy is a strategic effort to encourage regional autonomy in managing education in order to create a system that is more democratic and meets local needs. This article examines the opportunities and challenges of implementing education decentralization policies in Indonesia. Opportunities that arise include increasing the efficiency, effectiveness and relevance of education programs through the involvement of the community and local government. However, various challenges are also faced, such as regional capacity gaps, weak inter-governmental coordination, and lack of community participation. This study provides an overview of the importance of a collaborative approach in policy implementation, including capacity building, transparency and accountability, to realize higher quality and more equitable education throughout Indonesia.